«In versi latini all’improviso composti»: Preliminary notes for a history of Latin extemporaneous poetry in Arcadia (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
In outlining a profile of improvised poetry in Latin in Arcadia, with particular attention to the custodiati of Crescimbeni (1690-1728) and Morei (1743-1766), this essay proposes a detailed analysis of the documentation, in part already known in part unpublished, to focus the attention on some published improvised Latin texts, written by Arcadi Antonio de’ Felici, Antonio Somai, Antonio Re da Roma e Pietro Antonio Petrini. The essay provides the edition, translation and a comment of the sources. Lastly, considering the exceptional nature and importance of these witnesses - of which there are also other manuscripts, subject of ongoing research - the study wants to reflect on the ways of circulation and use of improvised poetry, even in the objective difficulty of framing the phenomenon.
Keywords: Extemporaneous Poetry; Latin Language; Crescimbeni; Morei; Antonio de' Felici; Antonio Somai; Antonio Re da Roma; Pietro Antonio Petrini